Morality and Relations before Hume - Stewart Duncan (Journal of Modern Philosophy)
In his Enquiry concerning the Principles of Morals, David Hume said that a group of earlier modern philosophers, beginning with Malebranche, held that morality was founded on relations. In this paper I follow up on that suggestion by investigating pre-Humean views in moral philosophy according to which morality is founded on relations. I do that by looking at the work of Nicolas Malebranche, John Locke, and Samuel Clarke. Each of them talked prominently about relations in their accounts of basic aspects of morality. Beyond that, each of them turns out to have held both metaphysical and epistemological views that might be described as founding morality on relations. Despite the definite differences between the three philosophers’ approaches, Hume does seem to have noticed a genuine connection here—even though he himself tended to ignore significant versions of this approach when criticizing it.